Gray Water Reuse in Florida - Christopher J. Martinez (EDIS, 2010)
AE453, a 5-page illustrated fact sheet by Christopher J. Martinez, provides an overview of the recycling of gray water, the ways that gray water can potentially be used, and the regulations and guidelines for gray water reuse in Florida, as well as discussion of some of the potential barriers to gray water reuse in Florida and elsewhere. Includes references. Published by the UF Department of Agricultural and Biological Engineering, January 2010.